A Role‑Based Document Verification and Authorization System with QR Code Integration for Campus Administrative Processes - Pinem, Sanjaya; El Rezen Purba, Doni; Yakob, Freddy (Cattleya Darmaya Fortuna, 2026)
Document authentication has become a critical necessity for various institutions to prevent forgery, such as data manipulation or page substitution. While QR code technology is widely used, many current implementations rely on static links lacking robust validation mechanisms, making them susceptible to exploitation. This study aims to develop a QR code-based document verification system with a centralized validation architecture that is practical and efficient for small-to-medium-sized institutions. The research methodology employs the Software Development Life Cycle (SDLC) Waterfall model, encompassing requirements analysis, system design, implementation, testing, and maintenance. The system is designed with a multi-role workflow (Admin, Lecturer, and Guest) where the QR code serves solely as a reference identity, while the actual validation occurs within a centralized database to minimize spoofing risks. Results from Black Box Testing confirm that the system effectively manages the document lifecycle, from initial upload to electronic signature (TTE) application and real-time public verification via unique URLs. This implementation demonstrates that centralized hash validation is a sufficient security measure to mitigate document forgery risks without requiring high-complexity infrastructure.